A sample of radio galaxies spanning three decades in radio luminosity - I. The host-galaxy properties and black-hole masses - McLure, R; Willott, C; Jarvis, M; Rawlings, S; Hill, G; Mitchell, E; Dunlop, J; Wold, M (2004)
The results of analysis of HST I-band imaging of a sample of 41 radio galaxies spanning three orders of magnitude in radio luminosity at redshift z~0.5 are presented. The full sample is drawn from four complete, low-frequency selected radio samples with progressively fainter flux-density limits (3CRR, 6CE, 7CRS and the new TexOx-1000 sample). Modelling of the HST imaging data shows that the host galaxies have surface-brightness distributions consistent with those expected for classic ellipticals (Sersic parameter, beta~0.25), with beta in the range 0.17<beta<0.30, <beta="" a="" and="" mean="" of="">=0.23±0.01. The host-galaxy luminosities are comparable with those of galaxies drawn from the bright end of the local cluster galaxy luminosity function, spanning the range 0.7L^{\star}<l<10l^{\star}, 0.0<z<0.8,="" 10^{8.1}\msun="" 10^{9.5}\msun,="" 3.2±0.3="" 3c-class="" <m_{bh}="" <m_{bh}<="" a="" addition,="" and="" are="" black="" black-hole="" central="" class="" combining="" converting="" do="" dynamical="" estimates="" evidence="" evolution="" follow="" for="" found="" from="" galaxies="" galaxies.="" galaxy="" geometric="" harbour="" holes="" host="" host-galaxy="" in="" indistinguishable="" interval.="" into="" is="" it="" kormendy="" l^{\star}.="" literature="" low-redshift="" luminosities="" mass="" masses="" mean="" new="" no="" not="" of="" our="" over="" powerful="" predicts="" providing="" radio="" range="" redshift="" relation="" relations="" results="" scalelengths="" shown="" significantly="" that="" the="" this="" those="" to="" vary="" with="" within="">=10^{8.87± 0.04}\Msun. Finally, a significant (~3 sigma) correlation is found between black-hole mass and 151-MHz radio luminosity for those objects in the sample with either high-excitation nuclear spectra or classical double radio structures. (abridged)</l<10l^{\star},></beta<0.30,>